PENGARUH PENGELOLAAN LABA TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DENGAN MEKANISME CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - Rochman Adi Bowo; Endang Kiswara (Diponegoro Journal of Accounting, 2014)
This research was aimed to examine empirically: (1) The influence of earningsmanagement to CSR disclosure (2) The role of corporate governance mechanism as moderating variable in the relationship between earnings management and CSR disclosure. Corporategovernance mechanism was analyzed by proportion of independent commissioner, the number ofaudit committee meetings and board size. Earnings management was measured by discretionary accruals use Modified Jones Model and the extent of CSR was measured used corporate social reporting index (CSRI) based on Global Reporting Initiative (GRI) reporting standard items which were disclosed in companies annual report. This research used samples of company listed on Indonesia Stock Exchange 2012-2013. Data obtained from annual reports and sustainable reports of manufacturing companies listed on the IDX. There are 65 companies among 2012-2013 which fulfilling. The method of analysis of this research was multiple regression. This method was chosen because the independent variables are more than one and all the data of the variables are metric.This reseach found no significant statistical effect from various measurement of earnings management to CSR disclosure. The research also found there is no significant effect on proportion of independent commissioner, board size, and the number of audit committee meetings in relationship between earnings management and CSR disclosure. This research concluded that CSR is driven by the desire to meet the expectation of stakeholders and not due to earnings management. In addition, the formation of the board of commissioners need to consider the composition of ability and integrity of the members so that they can perform the function of monitoring, control and able to provide direction to management as well.